Dataset of fish epidemiology and health economics in Ogun and Delta States - Khor, Laura; Delamare-Deboutteville, Jerome; Chadag, Vishnumurthy Mohan; Adeyemo, Olanike; Selim, Alarape; Sanmi, Aina; Hanson, Larry; Wills, Robert (2023)
Dataset of fish epidemiology and health economics in Ogun and Delta States to understand epidemiology and health economics of catfish and tilapia